2020
DOI: 10.1002/hep.31047
|View full text |Cite
|
Sign up to set email alerts
|

The von Willebrand Factor Facilitates Model for End‐Stage Liver Disease–Independent Risk Stratification on the Waiting List for Liver Transplantation

Abstract: Background and Aims The Model for End‐Stage Liver Disease (MELD) is used for clinical decision‐making and organ allocation for orthotopic liver transplantation (OLT) and was previously upgraded through inclusion of serum sodium (Na) concentrations (MELD‐Na). However, MELD‐Na may underestimate complications arising from portal hypertension or infection. The von Willebrand factor (vWF) antigen (vWF‐Ag) correlates with portal pressure and seems capable of predicting complications in patients with cirrhosis. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 46 publications
(59 reference statements)
8
46
0
Order By: Relevance
“…In particular, the identification of high-risk patients with low MELD-Na score at listing, as well as further stratification of patients with a very high MELD-Na score pose difficult challenges (7-10). We previously documented that vWF-Ag significantly improved prediction of 3month waitlist mortality (13). However, a previous report from our group that was based on a different patient population indicated that the combination of CRP and vWF-Ag is particularly powerful to predict outcome in end-stage liver disease patients (12).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In particular, the identification of high-risk patients with low MELD-Na score at listing, as well as further stratification of patients with a very high MELD-Na score pose difficult challenges (7-10). We previously documented that vWF-Ag significantly improved prediction of 3month waitlist mortality (13). However, a previous report from our group that was based on a different patient population indicated that the combination of CRP and vWF-Ag is particularly powerful to predict outcome in end-stage liver disease patients (12).…”
Section: Discussionmentioning
confidence: 84%
“…For the exploration cohort, all patients listed for LT between 2003 and 2016 at the Medical University of Vienna were included in this study. This particular set of patients was recently assessed for the relevance of vWF-Ag in 3-month waitlist mortality prediction and was now further evaluated (13). Routine blood samples at time of listing included baseline coagulation parameters, liver and kidney function tests as well as CRP and vWF-Ag levels.…”
Section: Study Population and Definition Of Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…Finally, VWF antigen levels have recently been shown to predict hepatic decompensation in patients with compensated cirrhosis (including patients with HCV-induced cirrhosis who had achieved sustained virologic response [SVR]) 94 and further improve model for end-stage liver disease (MELD)-Na-based risk stratification in patients listed for liver transplantation. 95 In addition, it may also predict liver failure following hepatectomy. 96 In summary, there is a plethora of simple blood-based biomarkers of portal hypertension; however, except for PLT (if combined with other parameters), none of the indirect markers of liver fibrosis markers is suitable for diagnosing CSPH in clinical practice.…”
Section: Blood-based Biomarkersmentioning
confidence: 99%